Organized hypocrisy, organizational façades, and sustainability reporting. (January 2015) - Cho, Charles H.; Laine, Matias; Roberts, Robin W.; Rodrigue, Michelle
Abstract: Sustainability discourse is becoming ubiquitous. Still, a significant gap persists between corporate sustainability talk and practice. Prior research on corporate sustainability reporting has relied primarily on two competing theoretical framings, signaling theory and legitimacy theory, which often produce contradictory results regarding the significance and effects of such disclosures. Thus, despite this substantial body of research, the role that sustainability disclosures can play in any transition toward a less unsustainable society remains unclear. In an effort to advance our collective understanding of voluntary corporate sustainability reporting, we propose a richer and more nuanced theoretical lens by drawing on prior work in organized hypocrisy (Brunsson, 1989) and organizational façades (Abrahamson & Baumard, 2008; Nystrom & Strabuck, 1984). We argue that contradictory societal and institutional pressures, in essence, require organizations to engage in hypocrisy and develop façades, thereby severely limiting the prospects that sustainability reports will ever evolve into substantive disclosures. To illustrate the use of these theoretical concepts, we employ them to examine the talk, decisions, and actions of two highly visible U.S.-based multinational oil and gas corporations during the time period of significant national debate over oil exploration in the Alaskan National Wildlife Refuge. We conclude that the concepts of organizational façade and organized hypocrisy are beneficial to the sustainability disclosure literature because they provide theoretical space to more formally acknowledge and incorporate how the prevailing economic system and conflicting stakeholder demands constrain the action choices of individual corporations.